OPTIMALISASI KINERJA TRUK QUESTER CWE 370 MELALUI MODIFIKASI SISTEM VESSEL - Pradani, Yayi Febdia; Tjiptady, Bella; Pratomo, Danang Yugo; Rahman, Rifki Zainur; Rohman, Mojibur (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2024)
The Quester CWE 370 truck is one of the most widely used transport vehicles in the industry, where reliability and operational efficiency are critical to ensuring a smooth supply chain. This research aims to optimize truck performance through vessel system modification, which focuses on improving fuel strength and efficiency. The modification process includes checking the raw material, cutting, welding, and smoothing, which is followed by testing to ensure fuel flow stability and better engine response. The results show that vessel system modifications not only improve fuel efficiency, but also extend engine life and reduce the need for routine maintenance. Thus, these modifications provide long-term benefits for the company in terms of operational cost savings and increased productivity.